Sexual violence and the healing process of the victims - PriyonoTri Febrianto; Aditya Dyah Puspitasari; Ade Cyntia Pritasari; Nilamsari Damayanti Fajrin; Siti Mas'udah; Lutfi Apreliana Megasari (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2022)
Sexual violence can occur anywhere and anytime. It can cause the victim to have prolonged trauma. This article aimed to examine the experiences of victims or survivors of sexual violence and to find out the healing process they carried out. This study employed a descriptive quantitative approach by interviewing 377 respondents. According to the findings of this study, sexual violence has various impacts on victims, including shame, low self-esteem, feelings of inferiority, and a desire to retaliate against the perpetrator. Fears that arise as a result of sexual violence include the fear of getting pregnant, contracting sexually transmitted diseases, sin, and feeling inferior. As a healing process, the victims engaged in a variety of activities ranging from worship to favorite activities to reduce trauma. This study concludes that the healing process is significant for victims, with the aim of accelerating both physical and psychological recovery.